Circulatory Adipokines and Incretins in Adolescent Idiopathic Scoliosis: A Pilot Study - Emilie Normand; Anita Franco; Nathalie Alos; Stefan Parent; Alain Moreau; Valérie Marcil (MDPI AG, 2022)
Adolescent idiopathic scoliosis (AIS) is a three-dimensional malformation of the spine of unknown cause that develops between 10 and 18 years old and affects 2-3% of adolescents, mostly girls. It has been reported that girls with AIS have a taller stature, lower body mass index (BMI), and bone mineral density (BMD) than their peers, but the causes remain unexplained. Energy metabolism discrepancies, including alterations in adipokine and incretin circulatory levels, could influence these parameters and contribute to disease pathophysiology. This pilot study aims to compare the anthropometry, BMD, and metabolic profile of 19 AIS girls to 19 age-matched healthy controls. Collected data include participants' fasting metabolic profile, anthropometry (measurements and DXA scan), nutritional intake, and physical activity level. AIS girls (14.8 ± 1.7 years, Cobb angle 27 ± 10°), compared to controls (14.8 ± 2.1 years), were leaner (BMI-for-age z-score ± SD: −0.59 ± 0.81 vs. 0.09 ± 1.11, p = 0.016; fat percentage: 24.4 ± 5.9 vs. 29.2 ± 7.2%, p = 0.036), had lower BMD (total body without head z-score ± SD: −0.6 ± 0.83 vs. 0.23 ± 0.98, p = 0.038; femoral neck z-score: −0.54 ± 1.20 vs. 0.59 ± 1.59, p = 0.043), but their height was similar. AIS girls had higher adiponectin levels [56 (9-287) vs. 32 (7-74) μg/mL, p = 0.005] and lower leptin/adiponectin ratio [0.042 (0.005-0.320) vs. 0.258 (0.024-1.053), p = 0.005]. AIS participants with a Cobb angle superior to 25° had higher resistin levels compared to controls [98.2 (12.8-287.2) vs. 32.1 (6.6-73.8), p = 0.0013]. This pilot study suggests that adipokines are implicated in AIS development and/or progression, but more work is needed to confirm their role in the disease.